2007
DOI: 10.2527/jas.2006-496
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the histochemical properties and meat quality traits of porcine muscles during the growing-finishing period as affected by feed restriction, slaughter age, or slaughter weight1

Abstract: In this study, the degree of contractile and metabolic development of myofibers in porcine LM, rectus femoris (RF), and dark and light portions of the semitendinosus (STD and STL, respectively) was determined, and their impact on meat quality was compared at the same age but different BW (trial 1) or at a given BW but different age (trial 2) in 48 Swiss Large White barrows from 12 litters after the growing and finishing period. The barrows had ad libitum (A) or restricted (R, 80% of A) feed access. In trial 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 43 publications
4
40
1
1
Order By: Relevance
“…In agreement with our results, reduced meat lightness and water loss have been observed in outdoor pigs by Pugliese et al (2005), whereas Bee et al (2004) reported lower meat lightness but higher drip in outdoor v. indoor pigs. Despite higher pH1 and pHu and lower drip, which have all been positively associated with mechanical tenderness of pork (Huff-Lonergan et al, 2002;Bee et al, 2007), BE pigs had higher meat shear force values than BC pigs. This cannot be ascribed to the amount or solubility of LM collagen, which did not differ between groups, but may be related to the trend (P = 0.11) for lower IMF in BE pigs, in agreement with the welldescribed negative relationship between IMF content and shear force of pork, especially for IMF values above 2.5% (De Vol et al, 1988;Lebret, 2009).…”
Section: Meat Quality Indicatorsmentioning
confidence: 90%
“…In agreement with our results, reduced meat lightness and water loss have been observed in outdoor pigs by Pugliese et al (2005), whereas Bee et al (2004) reported lower meat lightness but higher drip in outdoor v. indoor pigs. Despite higher pH1 and pHu and lower drip, which have all been positively associated with mechanical tenderness of pork (Huff-Lonergan et al, 2002;Bee et al, 2007), BE pigs had higher meat shear force values than BC pigs. This cannot be ascribed to the amount or solubility of LM collagen, which did not differ between groups, but may be related to the trend (P = 0.11) for lower IMF in BE pigs, in agreement with the welldescribed negative relationship between IMF content and shear force of pork, especially for IMF values above 2.5% (De Vol et al, 1988;Lebret, 2009).…”
Section: Meat Quality Indicatorsmentioning
confidence: 90%
“…By contrast, allometric growth coefficients of muscles involved with posture, such as the LM, are higher. Thus, they may be regarded as developmentally retarded muscles (Bee et al, 2007). As the second vaccination reduces the anabolic potential in the late finishing period, LM development might be more affected than ham and shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…Both samples were then cooked on a grill plate (Beer Grill AG, Zurich, Switzerland) at 190 to 1958C, to an internal temperature of 698C, and cooking losses were measured. Using a Warner-Bratzler shear device (Model 3000, G-R Electric Mfg Co., Manhattan, KS, USA), shear force was measured as described earlier (Bee et al, 2007). From each carcass, adipose tissue samples (both layers) were collected at the 10 to 14th-rib level, vacuum-packaged and stored at 2208C until further analysis.…”
Section: Meat Quality Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a Warner-Bratzler shear device (Model 3000; G-R Electric Mfg. Co., Manhattan, KS, USA), shear force values were determined as previously described (Bee et al, 2007). In addition, adipose tissue (both layers) was sampled at the 10th to 13th rib level, vacuum-packed and stored at 2208C until further analysis.…”
Section: Growth Trail and Carcass Measurementsmentioning
confidence: 99%